Urbanization and religion in ancient Central Mexico - Carballo, David M. ca. 20./21. Jh (Oxford University Press, 2015)
This volume examines the ways in which urbanisation and religion intersected in pre-Columbian central Mexico. It provides a materially informed history of religion and an archaeology of cities that considers religion as a generative force in societal change
Includes bibliographical references and index
Keywords: Indians of Mexico / Mexico / Mexican Plateau / Antiquities; Indians of Mexico / Mexico / Mexican Plateau / Urban residence; Indians of Mexico / Mexico / Mexican Plateau / Religion; Indians of Mexico / Mexico / Mexican Plateau / Social life and customs; Cities and towns, Ancient / Mexico / Mexican Plateau; Urbanization / Mexico / Mexican Plateau / History / To 1500; Social change / Mexico / Mexican Plateau / History / To 1500; Excavations (Archaeology) / Mexico / Mexican Plateau; Social archaeology / Mexico / Mexican Plateau; Stadt; Religion; Präkolumbische Zeit; Indianer; Mexican Plateau (Mexico) / Antiquities; Zentralmexiko